Preventing neglected club feet in Uganda: A challenge to the health workers with limited resources - Naddumba, E. K. (African Journals Online (AJOL), 2010)
Neglected clubfoot deformity is one of the commonest musculoskeletal disorders in Uganda. It is as a result of failure to provide treatment to the congenital clubfoot deformity during the infancy period due to limited resources. The incidence of clubfoot in Uganda is estimated to be 1/1000,like elsewhere, globally. The population of neglected clubfeet in the country is approximately 10,000. There are 20 orthopaedic surgeons in the country with a population of 28 million. The treatment in the past has been surgical after failed conservative treatment. With limited resources it is not possible to attend to all clubfeet in the country that would require surgery. The Social economic impact of failure to treat this deformity is great resulting in poverty to the families, and the country. The Uganda Sustainable Clubfoot Project has been established in the country whose Goal is to contribute to elimination of the neglected clubfoot in the country. The methodology is discussed in the presentation with a focus for developing capacity for early detection, treatment using the ponseti method, raising awareness of the health workers and the public, and political support.